2018
DOI: 10.1111/1755-6724.13506
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Stratigraphy and Rudist Facies Development of the Upper Barremian‐Lower Cenomanian Platform, Northern Sinai, Egypt

Abstract: The Lower Cretaceous sections in northern Sinai are composed of the Risan Aneiza (upper Barremian‐middle Albian) and the Halal (middle Albian‐lower Cenomanian) formations. The facies reflect subtle paleobathymetry from inner to outer ramp facies. The inner ramp facies are peritidal, protected to open marine lagoons, shoals and rudist biostrome facies. The inner ramp facies grade northward into outer ramp deposits. The upper Barremian‐lower Cenomanian succession is subdivided into nine depositional sequences co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…A similar microfacies has been identified in the Sarvak Formation in Zagros Basin by Ghabeishavi et al (2010), Mehrabi et al (2015), Assadi et al (2018) and Gholami Zadeh et al (2019). Also, this microfacies was recorded from Cenomanian strata of Iraq (Aqrawi et al, 1998;Mahdi et al, 2013;Al-Ali et al, 2019), Turkey (Mülayim, 2013;Mülayim et al, 2019;Özkan and Altiner, 2019), Mexico (Omaña et al, 2014), Jordan (Schulze et al, 2005) and Egypt (Salama et al, 2018).…”
Section: Microfacies Of the Sarvak Formation In The Pyun Sectionmentioning
confidence: 82%
See 2 more Smart Citations
“…A similar microfacies has been identified in the Sarvak Formation in Zagros Basin by Ghabeishavi et al (2010), Mehrabi et al (2015), Assadi et al (2018) and Gholami Zadeh et al (2019). Also, this microfacies was recorded from Cenomanian strata of Iraq (Aqrawi et al, 1998;Mahdi et al, 2013;Al-Ali et al, 2019), Turkey (Mülayim, 2013;Mülayim et al, 2019;Özkan and Altiner, 2019), Mexico (Omaña et al, 2014), Jordan (Schulze et al, 2005) and Egypt (Salama et al, 2018).…”
Section: Microfacies Of the Sarvak Formation In The Pyun Sectionmentioning
confidence: 82%
“…A similar microfacies has been documented in the Sarvak Formation in Zagros Basin by Ghabeishavi et al (2010), Mahmoudi Renani and Taheri (2012), Mahdi et al (2013), Mehrabi et al (2015), Rikhtegarzadeh et al (2016), Assadi et al (2018) and Gholami Zadeh et al (2019). Also, this microfacies has been identified in the Cenomanian strata of Iraq (Mahdi et al, 2013), Turkey (Mülayim et al, 2019;Solak et al, 2019), Oman (van Buchem et al, 1996Razin et al, 2017) and Egypt (Saber et al, 2009;Salama et al, 2018).…”
Section: Microfacies Of the Sarvak Formation In The Pyun Sectionmentioning
confidence: 89%
See 1 more Smart Citation
“…The fossil distribution, both stratigraphically and geographically, is highly predictable relative to the stratigraphic architecture, principles have been developed from numerical models (e.g., Holland 2000Holland , 2001Holland , 2012 and have been supported by numerous case studies, in both paleobiological and biostratigraphic research (e.g., Brett 1998;de Araujo Carvalho et al 2006;Smith et al 2006;Hewaidy et al 2013;Abdelhady and Fürsich 2015;Davtalab et al 2017;Salama et al 2018;Fung et al 2019;. Many authors found cyclic patterns of the biotic attributes of different faunal communities including Foraminifera, Mollusca, and Echinoidea, but research in bio-sequence stratigraphy (faunal-based sequence stratigraphic analyses), is still missing a standardized approach to be followed in defining high-resolution cycles and parasequences.…”
Section: Limitation and Future Prospectivementioning
confidence: 99%
“…Fig. 10d (from Salama et al 2018) Material: An anterior-posterior ls in the upright growth position was collected from the Barremian-Aptian at the Raghawi section.…”
Section: Family Polyconitidae Macgillavry 1937mentioning
confidence: 99%